Determining The Capacity of Temporary Evacuation Shelter in Carita and Labuan District Pandeglang Regency - Budianto Ontowirjo; Ardiansyah Ardiansyah; Dini Purbani; Muhammad Ramdhan; Hadiwijaya Lesmana Salim; August Daulat; Aida Heriati (Jurnal Segara, 2022)
A tsunami due to the GAK flank collapse occurred along the Sunda Strait Coast on December 22, 2018, with areas severely hit including Labuan and Carita Districts on the coast of Pandeglang Regency. The disaster resulted in the death of 431 people, more than 7200 injured and 46,646 people lost their homes. To anticipate the number of disaster casualties, disaster mitigation efforts are carried out using network analysis applications from GIS (Geographical Information Systems) software. The data used in the network analysis process is road data obtained from the Open Street Map in 2019 and supported by wave propagation and speed time to TES. This study used a walking speed of 0.751 m/second for elderly people. The results of the network analysis process showed the best route to the proposed Temporary Evacuation Shelter (TES). There are eight proposed TES in Carita District from which  seven are located on Raya Anyer Sirih Street and another one is located on Perintis Kemerdekaan. The number of residents in each area segment in the proposed TES is between 179 and 2,677 people. Yet, there are four existing TES units in Carita District located on Perintis Kemerdekaan Street. In Labuan District, one TES unit is proposed, which has the capacity of up to 4,376 people. Meanwhile, its existing TES is in the form of a Tsunami Shelter Building      with a capacity of 23,635 people.